2016
DOI: 10.1016/j.eucr.2015.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Stretch due to Penile Prosthesis Reservoir Migration

Abstract: A 43-year old patient presented to the emergency department with stretch, due to impossible deflation of the penile prosthesis, 4 years after successful implant. A CT-scan showed migration of the reservoir to the left rectus abdominis muscle. Refilling of the reservoir was inhibited by muscular compression, causing stretch. Removal and replacement of the reservoir was performed, after which the prosthesis was well-functioning again. Migration of the penile prosthesis reservoir is extremely rare but can cause s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Baten et al also reported on a case of reservoir migration from the right pre-peritoneal space to the left rectus abdominus muscle. 15 In a case series by Cui et al, two cases of IPP migration were reported: one in a patient with a history of bilateral inguinal hernia repair who had his prosthesis placed via a penoscrotal approach, and the other in a patient who had a history of prostatectomy whose prosthesis migrated to a subhepatic location. 16 Levine et al conducted a review of the literature, identifying 19 cases of erosion into the bladder and eight of erosion into the bowel.…”
Section: Discussionmentioning
confidence: 99%
“…Baten et al also reported on a case of reservoir migration from the right pre-peritoneal space to the left rectus abdominus muscle. 15 In a case series by Cui et al, two cases of IPP migration were reported: one in a patient with a history of bilateral inguinal hernia repair who had his prosthesis placed via a penoscrotal approach, and the other in a patient who had a history of prostatectomy whose prosthesis migrated to a subhepatic location. 16 Levine et al conducted a review of the literature, identifying 19 cases of erosion into the bladder and eight of erosion into the bowel.…”
Section: Discussionmentioning
confidence: 99%
“…These include compression of ureter leading to hydronephrosis,7 erosion of the reservoir into the bladder,9 migration of the reservoir into the left rectus abdominis muscle,10 migration of the reservoir into a subhepatic area, inguinal herniation of the reservoir,11 and retained reservoir leading to the formation of a large reactive cyst compressing the bladder 12. In a study and literature review performed by Rajpurkar et al .,8 prior pelvic surgery and infection were discovered to be risk factors for reservoir erosion.…”
Section: Commentmentioning
confidence: 99%